ECE Teachers’ Roles of Developing Numeracy Literacy in Special Needs Children: Numeracy Literacy in Children with Special Needs - Diana; Tasu’ah, Neneng; Zulfikasari, Sony; Martika, Tias (Program Studi Magister Pendidikan Anak Usia Dini, 2023)
Special needs ECE children should be prepared with early literacy and numeracy skills to strengthen their competencies during the transitional phase to primary school. To help this transitional phase, teachers can provide a variety of diverse play activities. This study aims to explore and evaluate the pedagogical strategies employed by teachers in reinforcing special needs children's literacy and numeracy, as a support to their transition process from ECE to primary year. The research applied a qualitative method with data collection techniques through interviews, observations, and documentation. The sample selection applied purposive sampling based on the criteria and objectives of this study. The sample consisted of inclusive classroom teachers from ten ECE institutions in five regions of Central Java, including Semarang City, Pekalongan City, Surakarta City, Wonosobo District, and Jepara District. The study concludes that ECE teachers still see several limitations in dealing with special needs children. Therefore, teachers should modify plans and play activities to strengthen literacy and numeracy skills for special needs children to help them embark on primary school. Teachers expect necessary support for their improvement through training and guidance in dealing with special needs children, especially in developing their literacy and numeracy. Keywords: literacy and numeracy, special needs children, ECE-primary school transition References: 1 Agustina, E., & Zayyadi, M. (2023). Kemampuan Literasi Numerasi Siswa di Sekolah Inklusi. Apotema: Jurnal Program Studi Pendidikan Matematika, 9(1), 15-20. Alberta. (2019). Literacy and Numeracy Proggression. Understanding Special Education Needs, 1-15. Atlar, H., & Uzuner, Y. (2023). Supporting Teacher Development about Early Literacy in Children with Hearing Loss: An Action Research in Turkey. European Journal of Special Education Research, 9(2), 92-121. https://doi.org/https://doi.org/10.46827/ejse.v9i2.4832 Aunio, P., & Räsänen, P. (2016). Core numerical skills for learning mathematics in children aged five to eight years – a working model for educators. European Early Childhood Education Research Journal, 24(5), 684-704. https://doi.org/10.1080/1350293X.2014.996424 Barham, A. I., Ihmeideh, F., Al-Falasi, M., & Alabdallah, A. (2019). Assessment of first-grade students’ literacy and numeracy levels and the influence of key factors. International Journal of Learning, Teaching and Educational Research, 18(12), 174-195. https://doi.org/https://doi.org/10.26803/ijlter.18.12.11 BBPMP, B. B. P. M. P. P. J. T. (2022). Capaian Literasi, Numerasi, Dan Karakter Siswa Di Provinsi Jawa Tengah Tahun 2021. https://bbpmpjateng.kemdikbud.go.id/capaian-literasi-numerasi-dan-karakter-siswa-di-provinsi-jawa-tengah-tahun-2021 Brandenburg, R., McDonough, S., Burke, J., & White, S. (2016). Teacher Education Research and the Policy Reform Agenda. In R. Brandenburg, S. McDonough, J. Burke, & S. White (Eds.), Teacher Education: Innovation, Intervention and Impact (pp. 1-14). Springer Singapore. https://doi.org/10.1007/978-981-10-0785-9_1 Brooks-Gunn, J., & Markman, L. B. (2005). The Contribution of Parenting to Ethnic and Racial Gaps in School Readiness. The Future of Children, 15(1), 139-168. http://www.jstor.org/stable/1602666 BSKAP. (2022). Modul 3 Bagaimana Membangun Kemampuan Literasi. Comunitity Child Care Victoria. (2011). Early Literacy and Numeracy Self-Guided Learning Package. In: Australia. Davenport, L. A. (2012). Numeracy in inclusive early childhood classrooms: embedding learning opportunities and using effective instructional strategies. Department of Education and Early Childhood Development. ( 2009). Victorian Early Years Learning and Development Framework: For all children from birth to eight years. Department of Education and Early Childhood Development. Diana, Sunardi, Gunarhadi, & Yusuf, M. (2020a). The development of I-Teach model to improve early childhood teachers professionalism. Cypriot Journal of Educational Sciences, 15(6), 1614–1628. https://doi.org/10.18844/CJES.V15I6.5321 Diana, Sunardi, Gunarhadi, & Yusuf, M. (2020b). Preschool Teachers’ Attitude Toward Inclusive Education in Central Java, Indonesia. Icliqe, 1361–1368. https://doi.org/10.2991/assehr.k.200129.166 Elliott, L., Zheng, P., & Libertus, M. (2021). Individual Differences in Parental Support for Numeracy and Literacy in Early Childhood. Education Sciences, 11(9), 541. https://www.mdpi.com/2227-7102/11/9/541 Fatmawati, E., & Safitri, E. (2020). Kemampuan Literasi Informasi dan Teknologi Mahasiswa Calon Guru Menghadapi Pembelajaran di Era Revolusi Industri 4.0. Edukasi: Jurnal Pendidikan, 18(2), 214-224. https://doi.org/10.31571/edukasi.v18i2.1863 Fontil, L., Gittens, J., Beaudoin, E., & Sladeczek, I. E. (2020). Barriers to and Facilitators of Successful Early School Transitions for Children with Autism Spectrum Disorders and Other Developmental Disabilities: A Systematic Review. Journal of Autism and Developmental Disorders, 50(6), 1866-1881. https://doi.org/10.1007/s10803-019-03938-w Fontil, L., Sladeczek, I. E., Gittens, J., Kubishyn, N., & Habib, K. (2019). From early intervention to elementary school: A survey of transition support practices for children with autism spectrum disorders. Research in Developmental Disabilities, 88, 30-41. https://doi.org/https://doi.org/10.1016/j.ridd.2019.02.006 Haerudin, H. (2021). Pengaruh Literasi numerasi Terhadap Perubahan Karakter Siswa. Prosiding Sesiomadika, 1(1a). https://journal.unsika.ac.id/index.php/sesiomadika/article/view/2123 Imtiyas, I. A. R., & Simatupang, N. (2022). The Effect of Early Childhood Teacher's Educational Background on the Ability to Manage Children’s Learning: Evidence From Learning Process During Covid 19 Pandemic. Golden Age: Jurnal Ilmiah Tumbuh Kembang Anak Usia Dini, 7(2), 67-76. https://doi.org/10.14421/jga.2022.72-02 Indah, W. (2023). Analisis Kemampuan Literasi Numerasi Berdasarkan Gaya Belajar pada Anak Usia Dini. Jurnal Obsesi: Jurnal Pendidikan Anak Usia Dini, 6(6), 5840-5849. Jurmang, J. L. (2014). Teacher competencies for inclusive education: The case of management and instructional function. National Journal of Inclusive education, 2(1). Justice, L. M., Jiang, H., & Strasser, K. (2018). Linguistic environment of preschool classrooms: What dimensions support children’s language growth? Early Childhood Research Quarterly, 42, 79-92. https://doi.org/https://doi.org/10.1016/j.ecresq.2017.09.003 Keily, T., Evans, A., & Atchison, B. (2019). Strengthening the Early Childhood Education Continuum. Policy Guide. Education Commission of the States. Khasanah, I., & Purnamasari, I. (2023). Role-Playing Methods: Efforts to Stimulate the Development of Early Childhood Numeracy Literacy. Journal of Social Research, 2(4), 1074-1078. https://doi.org/https://doi.org/10.55324/josr.v2i4.776 Kokkalia, G., Drigas, A. S., Economou, A., & Roussos, P. (2019). School Readiness From Kindergarten to Primary School. Int. J. Emerg. Technol. Learn., 14(11), 4-18. Kurnianingsih, I., Rosini, R., & Ismayati, N. (2017). Upaya peningkatan kemampuan literasi digital bagi tenaga perpustakaan sekolah dan guru di wilayah Jakarta pusat melalui pelatihan literasi informasi. Jurnal Pengabdian Kepada Masyarakat, 3(1), 61-76. Kurniastuti, I., Evanjeli, L. A., & Sari, D. P. (2023). Teachers’ Challenges and Strategies in Teaching Literacy Skills for Children with Special Needs. Jurnal Obsesi: Jurnal Pendidikan Anak Usia Dini, 7(1), 937-948. https://doi.org/https://doi.org/10.31004/obsesi.v7i1.3598 Manning, M., Garvis, S., Fleming, C., & Wong, G. T. W. (2017). The relationship between teacher qualification and the quality of the early childhood education and care environment. Campbell Systematic Reviews, 13(1), 1-82. https://doi.org/https://doi.org/10.4073/csr.2017.1 Mazzotti, V. L., Rowe, D. A., Kwiatek, S., Voggt, A., Chang, W.-H., Fowler, C. H., Poppen, M., Sinclair, J., & Test, D. W. (2021). Secondary Transition Predictors of Postschool Success: An Update to the Research Base. Career Development and Transition for Exceptional Individuals, 44(1), 47-64. https://doi.org/10.1177/2165143420959793 Mumpuniarti, M. (2017). Challenges faced by teachers in teaching literacy and numeracy for slow learners. Journal of Sustainable Development, 10(3), 243. https://doi.org/https://doi.org/10.5539/jsd.v10n3p243 Ningsih, S., Gunayasa, I. B. K., & Dewi, N. K. (2022). Pengaruh Literasi Numerasi Terhadap Hasil Belajar Matematika Pada Siswa Kelas III SDN Lingkok Lima Tahun Ajaran 2021/2022. Jurnal Ilmiah Profesi Pendidikan, 7(3c), 1938-1943. https://doi.org/10.29303/jipp.v7i3c.881 Nurhayani, N., & Nurhafizah, N. (2022). Media dan Metode Pengembangan Literasi Anak Usia Dini di Kuttab Al Huffazh Payakumbuh. Jurnal Basicedu, 6(6), 9333-9343. Park, M.-H., Dimitrov, D. M., & Park, D.-Y. (2018). Effects of Background Variables of Early Childhood Teachers on Their Concerns About Inclusion: The Mediation Role of Confidence in Teaching. Journal of Research in Childhood Education, 32(2), 165-180. https://doi.org/10.1080/02568543.2017.1417926 Purab, S. M., & Purwono, A. (2022). Pengaruh Program Literasi Terhadap Keterampilan Menulis Siswa Kelas Iv a Mi Darussalam Pacet Mojokerto. Aulada : Jurnal Pendidikan Dan Perkembangan Anak, 3(2), 133–151. https://doi.org/10.31538/aulada.v3i2.972 Rachmat, M., Otong, S., Yubaedi, S., & Nur, R. (2017). Pengaruh Intensi, Motivasi, dan Pemahaman Guru terhadap Impementasi Pendidikan Inklusif. Jurnal Pendidikan Usia Dini, 11(2). https://doi.org/10.21009/JPUD.112.08 Rehalat, A., & Nurul 'ainy, Z. (2022). The Effect of Education Background Teacher on The Learning Process In Class At Muhammadiyah First Middle School Ambon. Perspektif Pendidikan dan Keguruan, 13(2), 81-87. https://doi.org/10.25299/perspektif.2022.vol13(2).10592 Salminen, J., Khanolainen, D., Koponen, T., Torppa, M., & Lerkkanen, M.-K. (2021). Development of Numeracy and Literacy Skills in Early Childhood—A Longitudinal Study on the Roles of Home Environment and Familial Risk for Reading and Math Difficulties [Original Research]. Frontiers in Education, 6. https://doi.org/10.3389/feduc.2021.725337 Sanches, T. (2018, 2018//). Required Skills for Teachers: Information Literacy at the Top. Information Literacy in the Workplace, Cham. Sari, D. Y. (2017). Peran guru dalam menumbuhkan literasi melalui bermain pada Anak Usia Dini. Golden Age: Jurnal Pendidikan Anak Usia Dini, 1(2). https://doi.org/10.29313/ga.v1i2.3316 Setiawan, A. (2018). Meningkatkan Kemampuan Berhitung Anak Usia Dini melalui Media Pembelajaran Matematika di RA Ma’arif 1 Kota Metro. SELING: Jurnal Program Studi PGRA, 4(2), 181-188. https://doi.org/https://doi.org/10.29062/seling.v4i2.309 Shvartsman, M., & Shaul, S. (2023). The Role of Working Memory in Early Literacy and Numeracy Skills in Kindergarten and First Grade. Children, 10(8), 1285. https://www.mdpi.com/2227-9067/10/8/1285 Stein, K., Veisson, M., Õun, T., & Tammemäe, T. (2019). Estonian preschool teachers’ views on supporting children’s school readiness. Education 3-13, 47(8), 920-932. https://doi.org/10.1080/03004279.2018.1539113 Suryawati, E. A., & Akkas, M. (2021). Buku Panduan Guru Capaian Pembelajaran Elemen Dasar-Dasar Literasi dan STEAM untuk Satuan PAUD. Pusat Kurikulum dan Perbukuan Badan Penelitian dan Pengembangan dan Perbukuan Kementerian Pendidikan, Kebudayaan, Riset, dan Teknologi. Titi, C., & Siti, A. (2022). ECE Educator Training: How to Develop Literacy and Environment Education for Children? Jurnal Pendidikan Usia Dini, 16(1). https://doi.org/10.21009/JPUD.161.09 Trainor, A. A., Carter, E. W., Karpur, A., Martin, J. E., Mazzotti, V. L., Morningstar, M. E., Newman, L., & Rojewski, J. W. (2020). A Framework for Research in Transition: Identifying Important Areas and Intersections for Future Study. Career Development and Transition for Exceptional Individuals, 43(1), 5-17. https://doi.org/10.1177/2165143419864551 Wackerle-Hollman, A. K., Durán, L. K., & Miranda, A. (2020). Early Literacy Skill Growth in Spanish-Speaking Children With and At Risk for Disabilities in Early Childhood. Topics in Early Childhood Special Education,40(1), 24-38. https://doi.org/10.1177/0271121420906469 Winarsih, S., Hendra, J., Idris, F. H., & Adnan, E. (2013). Panduan penanganan anak berkebutuhan khusus bagi pendamping (orang tua, keluarga, dan masyarakat). Kementrian Perlindungan Anak dan Perempuan. Yin, M., Condelli, L., Ogut, B., & Cronen, S. (2013). The Importance of Teacher Background Qualifications for Student Learning. American Institutes for Research. Zhao, X. (2017). Transition from kindergarten to elementary school: Shanghai’s experience and inspiration. Creative Education, 8(3), 431-446. https://doi.org/10.4236/ce.2017.83033